Late Neoproterozoic/Cambrian high-pressure mafic granulites from the Grove Mountains, East Antarctica: P-T-t path, collisional orogeny and implications for assembly of East Gondwana - Liu, Xiaochun; Hu, Jianmin; Zhao, Yue; Lou, Yuxing; Wei, Chunjing; Liu, Xiaohan (Precambrian Research, 2009)
The Grove Mountains are an inland continuation of the Late Neoproterozoic/Cambrian Prydz Belt of East Antarctica. In this paper we report high-pressure (HP) mafic granulites that occur in glacial moraines from this area. Petrographical textures, mineral compositions and P-T pseudosection calculations in the system NCFMASHTO (Na2O-CaO-FeO-MgO-Al2O3-SiO2-H2O-TiO2-Fe2O3) suggest that the HP mafic granulites record peak P-T conditions of 11.8-14.0 kbar and 770-840 degrees C. The post-peak evolution of these rocks involved near-isothermal decompression of ca. 6 kbar followed by a greenschist facies overprint. SHRIMP U-Pb zircon dating, coupled with the identification of mineral inclusion assemblage in zircons, reveals HP metamorphism occurred at ca. 545 Ma and subsequent retrograde reactions involving near-isothermal decompression at ca. 530 Ma. Garnet-clinopyroxene-whole-rock Sm-Nd isotopic analyses also yield Cambrian 'isochron' ages. This reflects collision at a convergent plate margin followed by extensional exhumation as the orogen collapsed during Late Neoproterozoic/Cambrian orogeny. Therefore, the occurrence of HP mafic granulites from the Grove Mountains provides evidence for a collisional tectonic setting for the Prydz Belt, which supports the notion that East Gondwana was not finally assembled until the Cambrian. (C) 2009 Elsevier B.V. All rights reserved. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000271362800012&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 24 REVIEW 1-2 181-199 174